Critical signals for grassland desertification prediction in the transition zone between desert and typical steppe in InnerMongolia, China - Baoping Meng; Zhuoyan Jin; Jin Chen; Yili Kuang; Shuhua Yi; Yanyan Lv; Jinrong Li (Ecological Indicators)
Global climate change and intensifying human activities have driven an accelerated desertification of grasslands in arid and semi-arid regions. Recent theoretical investigations have proposed that vegetation patches can serve as indicators of desertification. However, knowledge regarding the appropriateness of these proposed indicators still lacked. Understanding the relations between patch features and plant species diversity are crucial for the early prediction of desertification. In this research, the transition zone between desert and typical steppe in Inner Mongolia, China was studied. We analyzed vegetation patch features (including percentage of landscape (PLAND), patch density (PD), largest patch index (LPI), and perimeter-area ratio distribution (PARA)), species diversity indices (Shannon-Wiener, Simpson, Margalef, Pielou), soil seed bank density, similarity index, and established their relations. Results showed that: (1) During grassland desertification, LPI decreasing rapidly followed by a slower decline, while PARA exhibited an initial slow decrease before a rapid decline during grassland desertification, reaching a critical point at a vegetation coverage of 49.95 %. (2) Species diversity indices tended to be increased first and then decreased with the decrease of CA, LPI, and PARA. These variations followed a unimodal pattern (P < 0.001), with peak plant diversity indices observed at CA of 5 m2, LPI of 40 %, and PARA of 40. (3) Soil seed bank density and similarity were also increased first and then decreased (P < 0.001) with the process of grassland desertification. When CA was 6 m2, LPI was 40 %, PARA was 40, the soil seed bank density and similarity reached highest (with 900 seeds/m2, and similarity of 58 %, respectively). Our studies concluded that LPI and PARA could be considered as early warning signals of grassland desertification in transition zone, and provided scientific basics for grassland management in arid and semi-arid areas.